Substituted metal carbonyls. XVI. X-ray photoelectron spectroscopic differentiation of chemically distinct phosphorus environments in unidentate complexes of 1,1′-bis(diphenylphosphino)ferrocene - Chan, H.S.O. (2014)
Journal of Organometallic Chemistry